A comprehensive review on dynamic risk analysis methodologies. (May 2022) - Raveendran, Anagha; Renjith, V.R.; Madhu, G.
Abstract: There have been many advancements and developments in hazard and risk analysis techniques over the past several decades. Since then, many researchers integrated various dynamic aspects into the conventional static analysis of hazard and risk associated with various failure cases and accidents. Dynamic Risk Analysis is an advanced continuous real-time approach that deals with rapidly changing circumstances to update and integrate the changing risk levels into overall risk profile. The emergence of various dynamic frameworks and methodologies is a solution against the restrictions on conventional static hazard identification and risk estimation techniques. DRA may be applied throughout the lifetime of a dynamic system or process starting from its design stage ensuring safe operations, easy maintenance and test activities. It can also support a real-time risk-informed decision-making and risk management. Despite its advantages, the dynamic approaches may possess many challenges and limitations necessitating a comprehensive literature review on the evolution of various DRA techniques. A better understanding of the current trend of dynamic methodologies is also necessary to explore the scope of application of more advanced hybrid dynamic methodologies for an effective real-time health, safety and environment management. Highlights: Literature review on the evolution of static hazard identification and risk analysis methods into advanced dynamic models. A brief study on foundational contributions and historical perspective of Dynamic Risk Analysis (DRA) methodologies. Analyse the current trend of hybrid dynamic models and procedures for mapping static models into dynamic models. Study of major advantages and challenges in the DRA methods to identify further opportunities for future researches.